Application of Science and Technology of Goods Inventory Information System in the Ellisya Online Store - Syahril; Kalvin Paulinus Simbolon; Anggi Oktaviani (SAN Scientific, 2023)
This research aims to identify business needs related to inventory management of goods at Ellisya stores. Developing a goods inventory information system starting from designing, developing and implementing an information system using information technology principles in managing goods inventory. Increase the accuracy of inventory predictions by assessing information systems' ability to predict inventory needs accurately. Assessing data security and protection by ensuring that the information system complies with data security standards. It provides adequate protection against potential threats to the security of inventory data. Provide recommendations for developing a website-based goods inventory information system. The research method used in this research is the Waterfall development method. This method was chosen because of its clarity and structured stages, which greatly support technology integration to increase inventory management efficiency and accuracy. The research results show that applying technological knowledge in the Goods Inventory Information System using the Waterfall method positively impacts operational efficiency, more accurate inventory predictions, data security, user satisfaction, and financial well-being. Therefore, applying science and technology is an important step to improve the performance and competitiveness of organizations in managing inventory. The research results provide practical implications for improving operational efficiency in inventory management. S&T integration enables real-time monitoring, automation of administrative tasks, and more efficient stock management. The application of science and technology results in stronger data protection, having a positive impact on company reputation and customer trust. The novelty of this research lies in an integrative approach between the application of science and technology and the Waterfall development method. It provides a new perspective on how technology can be applied in the context of structured system development, namely by developing a website-based inventory information system for goods at Ellisya stores